2008
DOI: 10.1016/j.neuropharm.2007.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of nicotinic acetylcholine receptor expression in the caudal nucleus of the solitary tract

Abstract: The nucleus of the solitary tract (NTS) is the principal integrating relay in the processing of visceral sensory and gustatory information. In the present study, patch-clamp electrophysiological experiments were conducted using rat horizontal brainstem sections. Pre-synaptic and somatic/ dendritic nicotinic acetylcholine receptors (nAChRs) expressed in neurons of the caudal NTS (cNTS) were found to be randomly distributed between pre-synaptic and somatic/dendritic sites (χ 2 =0.72, df =3, p>0.87, n=200). Pre-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 53 publications
1
35
1
Order By: Relevance
“…Electrophysiological recordings from the NTS in brainstem slices revealed that nAChRs and mAChRs are likely expressed by different NTS neurons (43, 55). Moreover, subsets of small (somal area, ϳ137 m 2 ), elongated (form factor, ϳ0.62) caudal NTS neurons have been found to express functional presynaptic ␣3␤4-containing (this will be referred to throughout as ␣3␤4*) nAChRs (44), whose activation by nicotine, a broad spectrum agonist of nAChRs, or cytisine, a potent agonist of ␤4*-nAChRs, was found to enhance synaptic release of glutamate via a presynaptic mechanism (44).The presence of presynaptic and/or preterminal nAChRs in the CNS has been previously documented (1,19,28,31,34,44,57). Several studies reported presynaptic and/or preterminal ␤2-containing (likely ␣4␤2*) nAChRs corresponding to high-affinity binding sites for nicotine (1,13,24,28,(32)(33)(34)42).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Electrophysiological recordings from the NTS in brainstem slices revealed that nAChRs and mAChRs are likely expressed by different NTS neurons (43, 55). Moreover, subsets of small (somal area, ϳ137 m 2 ), elongated (form factor, ϳ0.62) caudal NTS neurons have been found to express functional presynaptic ␣3␤4-containing (this will be referred to throughout as ␣3␤4*) nAChRs (44), whose activation by nicotine, a broad spectrum agonist of nAChRs, or cytisine, a potent agonist of ␤4*-nAChRs, was found to enhance synaptic release of glutamate via a presynaptic mechanism (44).The presence of presynaptic and/or preterminal nAChRs in the CNS has been previously documented (1,19,28,31,34,44,57). Several studies reported presynaptic and/or preterminal ␤2-containing (likely ␣4␤2*) nAChRs corresponding to high-affinity binding sites for nicotine (1,13,24,28,(32)(33)(34)42).…”
mentioning
confidence: 97%
“…The NTS plays a key role in the maintenance of autonomic homeostasis and projects within the brainstem [e.g., to the dorsal motor nucleus of the vagus (DMV) and the ventrolateral medulla] that support parasympathetic and sympathetic visceral reflexes (e.g., gastrointestinal and baroreflex), as well as to higher brain regions (e.g., the thalamus and the hypothalamus) that support behavioral and endocrine functions (2, 46). Therefore, modulation of neuronal activity and synaptic transmission in the NTS by biologically active compounds such as nicotinic agonists can have potent effects on basic autonomic functions and visceral reflexes.The NTS contains a highly heterogeneous population of neurons characterized by a broad spectrum of morphological, electrophysiological, and cytochemical properties and multiple projection targets (3,6,12,17,20,23,44,55). Expression of nicotinic and muscarinic acetylcholine receptors (nAChRs and mAChRs, respectively) also varies across the NTS region (44, 55).…”
mentioning
confidence: 99%
See 3 more Smart Citations